2012
DOI: 10.1016/j.ijid.2012.05.209
|View full text |Cite
|
Sign up to set email alerts
|

Clinical risk factors of severity and molecular epidemiology of respiratory syncytial virus circulating in Kuala Lumpur, Malaysia: a retrospective study of 21 years

Abstract: Background: polymorphism within regulatory regions of immune response genes can affect the level of gene expression. Gamma interferon (INF-g) is a cytokine that plays an important role in immune response to infection of hepatitis B virus (HBV). The aim of this study is to explore the association between the two single nucleotide polymorphisms (SNPs) within promoter (at positions -611G/A,-56T/C) of the gamma interferon receptor1 gene (INFGR1) and susceptibility to chronic HBV infection.Methods: A total of 400 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“… 19 Similar results cited by other authors and mentioned that there were no significant differences in terms of gender and ethnicity between patients infected with different viruses. 20 It was observed that clinical symptoms caused by different respiratory viruses were similar. Statistical analysis showed no relationships between genotypes of influenza A with clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“… 19 Similar results cited by other authors and mentioned that there were no significant differences in terms of gender and ethnicity between patients infected with different viruses. 20 It was observed that clinical symptoms caused by different respiratory viruses were similar. Statistical analysis showed no relationships between genotypes of influenza A with clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%